COVID-19 vaccines, mobility, and pandemic bureaucracies: Undocumented migrants' perspectives from Italy's Alpine border - Costanza Torre; Elizabeth Storer (Elsevier, 2023)
While scholars have noted the deeply unequal effects of the pandemic containment, there has been limited attempt to map the socio-political lives of vaccination policies, particularly from the perspective of undocumented persons moving at state margins. This paper explores how undocumented migrants, who were predominantly male travellers attempting to cross Italy's Alpine borders, encountered Covid-19 vaccines and contemporary legislation. Based on ethnographic observations and qualitative interviews with migrants, doctors, and activists at safehouses both on the Italian and French sides of the Alpine border, we trace how mobility centred decisions to accept or reject vaccines were significantly shaped by exclusionary border regimes. We move beyond the exceptional focus of the Covid-19 pandemic to show how centring visions of health connected to viral risk diverted attention from migrants' wider struggles to move to obtain safety. Ultimately, we argue for a recognition of how health crises are not merely unequally experienced, but may result in the reconfiguration of violent governance practices at state borders.